Work-School Conflict Among Working Students: The Role of Core Self-Evaluations as an Antecedent - Putri, Krismasita Surya; Artiawati, Artiawati; Adinata, Surya Prawira; Yolanda, Brigitta; Kiara, Eunika (LPPM Universitas 17 Agustus 1945 Samarinda, 2025)
This study examines and explains the relationship between core self-evaluations and work-school conflict in working students. This research uses a quantitative method with correlation tests. The participants of this research were 366 people who were obtained using an accidental sampling technique. The characteristics of participants are active students from undergraduate to doctoral level or equivalent, aged over 18 years, and working actively in an institution. The instruments used were Core Self-Evaluations Scale by Judge et al (2003) and Work-School Conflict Scale by Carlson et al (2000). The Spearman correlation tests show a significant negative relationship between the two variables (r= -.444**). More specific results show a significant relationship between core self-evaluations and two dimensions of work-school conflict. i.e. WIS Conflict (r= -.390**) and SIW Conflict (r= -.418**). Strain-based conflicts were also shown to have more significant correlations than time-based conflicts. In addition, gender and job tenure are also associated with work-school conflict. The implications of this research prove that working students who have better core self-evaluations tend to overcome problems in school and work more easily because they have a sense of better confidence and self-control to overcome situations that put pressure on two domains.